CAN PRODUCT LEADERSHIP BE A PREDICTOR OF A CUSTOMERâS LOYALTY? - Santosa, MS. Eric (Journal of Indonesian Economy and Business, 2014)
Leading companies commonly employ a particular strategy to cover a market. They mightchoose product leadership, service support excellence, customer intimacy strategy, as well as acombination of them.The use of these strategies is obviously to gain more customers, since the product becomes achoice as an effect of the brand equity strengthening. While firms are very concerned withcustomer loyalty to maintain a stable sales volume, a question arises whether the brand equityhas an effect on the customerâs loyalty. Logically, if a strategy can develop the productâs brandequity which in turn propels cutomers to buy it, it will hopefully improve customersâ loyalty aswell.Therefore, this study is designed to answer the questions, (1) which strategy (among thethree) adds power to the brand equity, (2) the brand equity is influential to the customerâsloyalty, and (3) the product leadership can predict the customerâs loyalty. Three antecedents ofbrand equity are employed, i.e. product leadership, service support excellence, and customerintimacy. These three variables, along with brand equity can also indicate as predictors ofcustomerâs loyalty. A sample consisting of 100 respondents withdrawn through a judgmentmethod. Data were analyzed by Amos 5.0 and SPSS 16.0. The results denote that the relationshipsbetween product leadership and customer intimacy to brand equity, also brand equity tocustomerâs loyalty are significant. On the contrary, the relationship of service supportexcellence to brand equity and the relationship of product leadership to customerâs loyalty aretrivial.Keywords: product leadership, service support excellence, customer intimacy, brand equity,customerâs loyalty